Freedom To Choose In Ryan Murphy's Movie Eat, Pray, Love (2010) An Existentialist Approach - SARI, SHOLIKHAH ARUM (2012)
This study is aimed to show freedom to choose in Eat, Pray, Love movie by using Existentialist Approach. The objectives of the study are, to analyze the movie based on the structural elements and describe the movie based on an existentialist approach. In conducting this study, the researcher uses qualitative research. The data of study is image and text taken from two data sources. The primary source is the Eat, Pray, Love movie itself directed by Ryan Murphy, released in 2010. While the secondary data source are from other materials taken from book, internet and journal which related to the study. The study comes to the following conclusions. First, structural elements of Eat, Pray, Love movie which consist of character and characterization, plot, setting, point of view, theme, casting, mise-en-scene, cinematography, sound and editing build in good production. Second, based on the existentialist analysis, the director Ryan Murphy wants to convey message that everyone has their own way and freedom to choose how to solve problem in the life and should take into account the risks which possibility occur.